Determinant Factors Influencing the Decisions of Generation Y And Z to Invest on Capital Markets - Mihaela TULVINSCHI; Anamaria-Geanina MACOVEI; Maria GHERMAN; Iulian DASCALU (Communications of International Proceedings, 2021)
Generations Y and Z (1980-2010) will acquire assets worth over $ 30 trillion in inheritance from previous generations over the next decade, which means that in short period, they will become the main players in the business environment. Because new generations have different values, we sought to explore which determinant factors are influencing the investment decisions of generations Y and Z on the capital market, by conducting a qualitative research, based on a questionnaire as research tool. The main objectives were: O1 Analyzing the need for non-financial information of generations Y and Z and O2 Develop a questionnaire for young students and graduates (generation Y and Z), in order to identify the influencing factors in the decision to invest on the capital markets. The results of this paper materialized in the design of a model which can be used for assessing non-financial factors that influence generations Y and Z decisions related to capital market. This can be useful to economic entities which are on the capital market, by disclosing based on which factors generations Y and Z make decisions, but also for academic environment, the latter being interested in training young people to make the best financial and sustainable decisions.
Keywords: CSR; Influencing Factors; Generation Y and Z; Non-financial information; Sustainability.